Hubungan Sosial Budaya, Kelengkapan Imunisasi dan Faktor Social Ekonomi dengan Kejadian Stunting pada Balita 0-59 Bulan di Wilayah Kerja Puskesmas Sikumana - Marliance Lewo Wolla; Pius Weramen; Sigit Purnawan (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Stunting is a public health problem that impacts physical growth, cognitive development, and the quality of future human resources. Various factors are suspected to be associated with stunting, including socio-cultural factors, completeness of basic immunizations, and family socio-economic status. This study aims to analyze the relationship between socio-cultural factors, completeness of basic immunizations, and socio-economic status with stunting in toddlers aged 0–59 months in the Sikumana Community Health Center (Puskesmas) work area. This study used an observational analytical design with a case-control approach. The study sample consisted of 128 respondents, consisting of case and control groups. Data were collected using a questionnaire and analyzed using the Chi-Square test at a 95% confidence level (α=0.05). The results showed that most mothers had no dietary restrictions during pregnancy (77.3%), most toddlers received complete basic immunizations, and most families had sufficient income. Bivariate analysis showed no association between cultural dietary restrictions and stunting (p=0.833; OR=1.093). There was a significant association between completeness of basic immunizations and stunting (p<0.001; OR=0.121), with toddlers with incomplete immunizations having a greater risk of stunting. Furthermore, there was no significant association between family income and stunting (p=0.480; OR=0.779). This study concluded that completeness of basic immunizations was associated with stunting, while cultural dietary restrictions and family income were not associated with stunting in toddlers aged 0–59 months in the Sikumana Community Health Center (Puskesmas) work area. Increasing coverage of complete basic immunizations is necessary to continue to prevent stunting.